(untitled) (Collaborate Engineering Daily Book Series, 2025)
The global energy paradigm shift from conventional to unconventional resources has ignited a profound debate on sustainability. This article explores the complexities of extracting unconventional energy such as shale gas, geothermal, and coal-bed methane within the framework of the three pillars of sustainable development: economic viability, social equity, and environmental integrity. Through a critical lens, it is argued that the rapid advancement of extraction technologies often outpaces regulatory frameworks and socio-ecological safeguards. This "fragile balance" is analyzed through the phenomena of negative externalities, agrarian conflicts, and market volatility. The article concludes that energy progress must be redefined not by production volume, but by systemic integrity and intergenerational justice.